The potential of light transmission using fibre optic cable for interior illumination in Malaysia - Norazalina Ismail (School of Environmental Engineering, University Malaysia Perlis, 2012)
This project discussed about the potential of light transmission using fiber optic cable (FOC) for interior illumination. Light system and method to a building is dark where a surface that allocated in building roof top can be penetrated with sunlight through a slice of a roof light. Solar energy is a part of widely recognized renewable energy sources; the solar energy sources is free of cost and clean energy whereby environmental impacts are negligible. In tropical countries like Malaysia, solar energy potential has been utilized in wide range of applications of remote and urban areas and has been growing rapidly. This research will alternatively examine and evaluate the potential of interior illumination using fiber optic cable. Based on literature study, light transmission using FOC is more relevant to use in decorative light. In realizing this project, I have invoked three methodologies to get that the relevant of reading, which is direct lamp source, insulated FOC and un-insulated FOC. Among this objective of the study is to identify the problem in illumination room by using FOC. Type of lamp bulb is using DC12v which is 5 watt, 18 watt and 30 watt. The experiment result show, the FOC is not suitable to be used for internal lighting. This is because rate of light brightness from FOC is 90% lowest compared normal lighting rate. The experiment result show the usage FOC give poor results to be compared with normal lighting. As conclusion, FOC is suitable to be used for decorative lighting system, underwater lighting in swimming pools and spas, backlighting of signage and landscape lighting.